Beliefs about medicines in patients with oral Rivaroxaban for the treatment of lower extremity deep venous thrombosis: A mixed-methods study (下肢深静脉血栓形成患者口服利伐沙班服药信念现状的混合研究) - YU Jie (于洁); JIN Xiaohong (金小红) (中西医结合护理)
Objective To investigate the Beliefs about Medicines in patients with oral Rivaroxaban for the treatment of lower extremity deep venous thrombosis, and to provide evidence for improving the quality of anticoagulation. Methods A mixed-methods study using questionnaires and cognitive interview was conducted. Totally 144 patients with deep venous thrombosis of lower extremity treated with oral Rivaroxaban anticoagulant were evaluated by a self-designed general information questionnaire and Beliefs about Medicines Questionnaire-specific (BMQ-specific), and 25 of them were interviewed by a semi-structured in-depth interview. Results The scores of necessity belief and concern belief about oral Rivaroxaban anticoagulant were (15. 14±3. 92) and (12. 60±3. 12) respectively, and the score of BMQ-specific was(2. 54±5. 09). According to the interview data, four main themes were refined as follows: Experience of anticoagulant efficacy, lack of cognition of adverse drug reactions, concern about adherence to medication, lack of continuity of medical education. Conclusion On one hand, patients accepted the need for anticoagulant medication; On the other hand, they had concerns about the potential risk of bleeding and other adverse reactions, and hope to stop the drugs as soon as possible. The medical staff should timely identify the adverse cognition of patients, strengthen medication education, and improve the quality of anticoagulant drugs. (目的 探讨下肢深静脉血栓形成患者口服利伐沙班的服药信念, 为提高抗凝质量提供依据。方法 本研究采用问卷调查与认知访谈相结合的方式, 自行设计一般资料调查表及使用特异性药物信念问卷调查表(BMQ-Specific), 对144名口服利伐沙班抗凝的下肢深静脉血栓形成患者进行问卷测评, 对其中25名患者进行半结构式深入访谈。结果 口服利伐沙班抗凝必要性维度得分为(15. 14±3. 92)分, 顾虑性维度得分(12. 60±3. 12)分, 服药信念得分(2. 54±5. 09)分。通过访谈资料构建出4个主要的主题: 抗凝疗效的体验、药物不良反应的认知不足、坚持用药的顾虑、医护宣教缺乏连续性。结论 患者认为服用抗凝药物是必要的, 但同时对抗凝药物可能发生的出血等不良反应存在疑问, 且希望能尽快停药。医护人员应及时识别患者的不良认知, 加强用药教育, 提高抗凝质量。)